Peran Label Halal dalam Keputusan Konsumen Memilih Obat : Studi Observasional di Apotek Enggal Saras Ungaran - Hussaana, Atina; Azida, Nining Farrikh; Marisa, Ana; Sholikhah, Anisatus (Indonesian Journal of Medical and Pharmaceutical Science, 2023)
Background: Islam has clear rules about halal products. For a Muslim, consuming halal products is a form of devotion to Allah SWT. The concept of halal and haram is the main point in people's consumption patterns. Like consuming food, consuming medicine must also be halal. This study was designed to learn about the proportion of halal-labeled drugs in Apotek Enggal Saras Ungaran and the influence of halal labels on consumer decisions to choose medicines. Methods: The research method uses a direct survey. The questionnaire was addressed to buyers at the Apotek Enggal Saras Ungaran who bought halal-labeled drugs and those not labeled as halal to determine the respondent's interest in halal-labeled products. Data collection is done by grouping the data according to the criteria and calculating the percentage of each group. Results: The use of halal-labeled drugs and drugs not labeled halal are 60% and 40%, respectively. Conclusion: Muslim consumers prefer halal products to those that are not labeled halal. Factors that determine community decision-making in choosing halal-labeled drugs at Apotek Enggal Saras Ungaran include knowledge of halal labels, price affordability, product evaluation, fulfillment of halal product needs, and alternatives in decisions to use halal drugs.